Comparing plasma levels of C-reactive protein, interleukin-10 and -15 in physically active and sedentary postmenopausal women Kane Ayntrlv - Mona Sarhadi; Mokhtar Nasiri Farsani; Kiana Hassanzadeh (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Lower levels of inflammatory cytokines and higher levels of anti-inflammatory cytokines are associated with increased life expectancy. However, the effects of regular physical activity on these cytokines in postmenopausal women have not been investigated very well.  Methods & Materials Fifteen active and 15 inactive postmenopausal women (aged between 50-60 years) were recruited randomly. The exclusion criteria included chronic diseases, smoking, and surgeries in the past year. Also, more than a year should have passed since all subjects experienced natural menopause. Active postmenopausal women should have regular physical activity included walking, jogging, and resistance exercises and they should have performed these exercises three times a week within the past 6-12 months. After 12 hours of fasting, blood samples were taken in rest. Blood sample was centrifuged at 4000 rpm for 5 minutes, and the serum was frozen and stored at -80°C until biochemical analyses were performed. Independent t test was used to compare quantitative variables, and α level for statistical significance was set at P ≤ 0.05. Results Regular physical activity brings about a significant decrease in C-reactive protein, significant increase in IL-15 and non-significant increase in IL-10 in active postmenopausal women in comparison to inactive postmenopausal women. Conclusion Regular physical activity may result in lower incidence of chronic diseases in postmenopausal women via decreased inflammatory cytokines and increased anti-inflammatory cytokines and could, therefore, play a role in higher life expectancy.